Pengaruh kegiatan rekreasi bermain kelompok dan kegiatan rekreasi bermain individu terhadap penurunan stres pada lansia - Ajeng (Jurnal Kesehatan, 2024)
Elderly or elderly are an age group in humans who have entered the final stages of their life phase and are susceptible to various complex problems such as health problems due to the aging process. The aging process can cause various physical, biological, socio-economic and mental problems. The characteristics that are clearly visible are a decrease in the body's ability to adapt to the surrounding environment such as: decreased functions of organs and body systems that are natural or physiological and decreased stress management. Stress is a state where a person experiences internal events and environmental situations that burden the ability to adapt. Stressful conditions can occur due to the inability of individuals to manage the pressure they face. The literature search method was carried out based on articles published between 2019-2024 according to the inclusion and exclusion criteria that have been set using the Google Scholar, Pubmed and Science Direct databases. From the search results, there were 220 articles according to keywords that were filtered into 6 journals according to the analyzed theme that examined the effect of group play recreation activities and individual play recreation activities on reducing stress in the elderly. From the results of the literature review of 6 journals, it was found that all recreational coping mechanism activities can reduce stress levels in the elderly. The more often the intensity of recreational play activities is carried out, the lower the stress level of the elderly will be.